Humeral Capitellum Fractures in Adolescents: A Study of 6 Cases Treated by Open Reduction and Internal Fixation with Bioabsorbable Nails - Łukasz Wiktor; Ryszard Tomaszewski (Advances in Orthopedics)
Purpose. The purpose of our study was to evaluate the clinical outcome following open reduction and internal fixation of humeral capitellum fractures in adolescents and to assess the usefulness of bioresorbable implants in that procedure. Due to the rarity of these fractures, there are not many studies dealing with the problem in the literature. Methods. We retrospectively evaluated a group of 6 skeletally immature patients aged 10.6–15.3 treated at our department from January 2015 to December 2021. Four type I and two type IV were diagnosed based on the Bryan and Morrey classification. Our patients underwent an open reduction and internal fixation of coronal shear fractures with the use of SmartNail®. Results. All patients were satisfied with the treatment outcome and had full pronation and flexion after surgery. Two patients presented minor deficits of extension and supination compared with the contralateral elbow. At the one-year follow-up, all patients scored 100 on the Mayo Elbow Performance Score. Conclusions. Correct diagnosis and early surgical intervention in humeral capitellum fractures are crucial. That fractures should be anatomically reduced with no articular cartilage damage in order to prevent osteoarthritis. Based on our experience, SmartNail® implant is accurate for the osteochondral fragment fixation.